2020
DOI: 10.1186/s12896-020-00638-7
|View full text |Cite
|
Sign up to set email alerts
|

Efficient generation of GGTA1-deficient pigs by electroporation of the CRISPR/Cas9 system into in vitro-fertilized zygotes

Abstract: Background: Xenoantigens are a major source of concern with regard to the success of interspecific xenografts. GGTA1 encodes α1,3-galactosyltransferase, which is essential for the biosynthesis of galactosyl-alpha 1,3-galactose, the major xenoantigen causing hyperacute rejection. GGTA1-modified pigs, therefore, are promising donors for pigto-human xenotransplantation. In this study, we developed a method for the introduction of the CRISPR/Cas9 system into in vitro-fertilized porcine zygotes via electroporation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 67 publications
2
37
1
1
Order By: Relevance
“…These oocytes have a low surface-to-volume ratio, making it difficult for LF2000 to move across the cell plasma membranes, resulting in low toxicity [ 24 , 25 ]. However, all mutated blastocysts derived from ZP-free oocytes treated with LF2000 were genetically mosaic upon the use of gRNAs targeting either PDX1 or GGTA1 , whose gene editing efficiency was confirmed in our previous study [ 19 , 20 ]. These results indicate that the timing of RNP introduction into oocytes may not be proper for producing biallelic mutant blastocysts.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…These oocytes have a low surface-to-volume ratio, making it difficult for LF2000 to move across the cell plasma membranes, resulting in low toxicity [ 24 , 25 ]. However, all mutated blastocysts derived from ZP-free oocytes treated with LF2000 were genetically mosaic upon the use of gRNAs targeting either PDX1 or GGTA1 , whose gene editing efficiency was confirmed in our previous study [ 19 , 20 ]. These results indicate that the timing of RNP introduction into oocytes may not be proper for producing biallelic mutant blastocysts.…”
Section: Discussionsupporting
confidence: 65%
“…In our lipofection-mediated system, gene-editing efficiency was insufficient compared with electroporation and microinjection-mediated gene editing [ 20 , 37 ], resulting in a low number of biallelic mutant blastocysts. Our previous study demonstrated that the results of electroporation- and microinjection-mediated gene editing were also affected by the concentration of CRISPR/Cas9 components, voltage strength during electroporation, and the developmental stage of zygotes/embryos [ 37 , 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, farm animals with point mutations and gene insertions (KI) have been successfully produced using ssODN donor sequences, CRISPR/Cas9 base editing and CRISPR/Cas9 nickase approaches ( Table 3 ). The applications of gene editing technologies for generation of livestock are very diverse, ranging from enhancing important production traits such as meat, milk, and fiber production ( Deng et al, 2014 ; Crispo et al, 2015 ; Hu et al, 2017 ; Zhou et al, 2017 ; Zhang R. et al, 2020 ) to improving disease resistance, health, reproductive efficiency, facilitating animal welfare, and developing new biomedical models to better understand the etiology of diseases and develop novel mechanism-based therapeutic approaches ( Vilarino et al, 2017 ; Fan et al, 2018a , b ; Tu et al, 2019 ; Tanihara et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…These improvements hold great promise for a rapid generation of transgenic mouse models, which will allow behavioral and functional screening at the level of F0 mice, and thus circumvent the need for long periods of cross-breeding. The genome editing of fertilized eggs by electroporation has been performed not only in mice but also in rats (Kaneko, 2017) and pigs (Tanihara et al, 2016(Tanihara et al, , 2020. In particular, it has been reported that the electroporation method for editing the genome of porcine fertilized eggs has several advantages over the microinjection method, such as shorter production time and reduced pre-and postnatal death rates (Tanihara et al, 2016).…”
Section: Rapid Generation Of Transgenic Micementioning
confidence: 99%